PHARMACOLOGICAL EFFICACY OF TRICHODESMA INDICUM (LINN) R. BR., IN FOLK MEDICINE â€“ AN UPDATED REVIEW - Mangai S, Alarmal (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â The medicinal knowledge of herbal plants plays a predominant role in finding new sources of drugs in pharmaceutics. The plant Trichodesma indicum (Linn) R. Br. is a significant constituent of Boraginaceae family with prominent records in conventional folk medicine. The diverse uses of the entire plant parts are being widely studied by in vitro and in vivo experimental methods. The present work is aspired to provide a biological evaluation of the plant that has been explored so far on various parts of the plant such as roots, leaves, and seeds. It also aims to provide a scientific support to the medicinal properties of the various phytoconstituents that are isolated from the plant. Hence, the present review is a comprehensive literature analysis of chemistry, ethanol-pharmacology and the therapeutic uses of T. indicum.